Research and implement on the intrusion tolerant system - YIN Li-hua; HE Song (Tongxin xuebao)
Intrusion tolerance technologies guarantee systems provided essential services by the fullest extent when some intrusions sneak into them.Architecture of an intrusion-tolerant system was proposed and intrusion tolerance technologies in node-level and system-level were practiced.Online intrusion diagnosis and redirection technology were researched to harden the system automatically.Experiment results illuminate that system providing service continuously can be set up and applied in the condition that does not require response time strictly but demands continuous implementation.